Study on Colour Reaction of Chromium(III) with 2-(2-Quinolinylazo)-resorcin using Microwave Radiation and its Application - Yang, Bo; Dong, Xuechang; Dai, Yun; Yang, Guangyu; Hu, Qiufen (Asian Journal of Chemistry, 2010)
A sensitive, selective and rapid method has been developed for the determination of chromium based on the colour reaction of Cr(III) with 2-(2-quinolinylazo)-resorcin (QAR). The Cr(III) can forms complex with QAR very slow at pH 5.5. However, irradiating the reacting mixture with microwave energy can markedly accelerate the complex formation. The absorbance reaches its maximum with 5 min of irradiation and remained stable at least for 24 h. Cetyl trimethyl-ammonium bromide (CTMAB) was used for increasing the sensitivity and solubility of the system. The molar absorptivity of the complex is 8.94 × 104 L mol-1 cm-1 at 590 nm. Beer’s law is obeyed in the range of 0.01-0.8 μg/mL. This method was applied to the determination of chromium(III) in biological samples, water and steel with good results.